2002
DOI: 10.1002/polb.10236
|View full text |Cite
|
Sign up to set email alerts
|

Melt blending of ethylene‐vinyl alcohol copolymer/clay nanocomposites: Effect of the clay type and processing conditions

Abstract: Ethylene-vinyl alcohol copolymer (EVOH)/clay nanocomposites were prepared via dynamic melt blending. The effect of the processing parameters on blends containing two clay types in different amounts was examined. The blends were characterized with a Brabender plastograph and capillary rheometer, differential scanning calorimetry, dynamic mechanical thermal analysis (DMTA), X-ray diffraction (XRD), transmission electron microscopy (TEM), and thermogravimetric analysis (TGA). XRD showed advanced EVOH intercalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…[25] Additionally, the silicate acted as a nucleating agent, causing the viscosity of the matrix to drop, decreasing the T m . [33] Artzi et al [19] observed the same occurrence of decreased T m with increasing clay content. The influence of nanoclay on the reduction of crystallization and melting behavior of PLA became distinct when the concentration of clay was around 3 wt % due to the intercalated nanostructure.…”
Section: Thermal Property Of Ts/pla/cloisite Na + Nanocompositesmentioning
confidence: 78%
See 1 more Smart Citation
“…[25] Additionally, the silicate acted as a nucleating agent, causing the viscosity of the matrix to drop, decreasing the T m . [33] Artzi et al [19] observed the same occurrence of decreased T m with increasing clay content. The influence of nanoclay on the reduction of crystallization and melting behavior of PLA became distinct when the concentration of clay was around 3 wt % due to the intercalated nanostructure.…”
Section: Thermal Property Of Ts/pla/cloisite Na + Nanocompositesmentioning
confidence: 78%
“…[17] The intercalated and exfoliated nanocomposites currently are of primary interest because their properties are significantly improved, even at low clay concentrations. However, the formation of intercalated or exfoliated nanocomposites depends on the type of organoclay, [9] [18] the clay content, [19] [20] and the processing conditions. [21] The objective of this study was to prepare tapioca starch (TS)/PLA/Cloisite NA + nanocomposite foams of different clay contents via melt-intercalation and to investigate the influence of clay content on selected structural, morphological, thermal, physical, and mechanical properties of the foams.…”
Section: Introductionmentioning
confidence: 99%
“…In thermoplastics the long chain molecules are held together by weak vander waal forces where as in thermosetting, the long chain molecules are held together by strong bonds. Some of the common thermoplastic polymers are; acrylonitrile butadiene styrene (ABS) [Zheng et al, 2004), Acrylic (PMMA) (Khaled et al ., 2007), Ethylene vinyl alcohol (EVOH) (Artz et al, (2002), Polyacrylonitrile (PAN) (Zhang et al, 2009), Polyamide-imide (PAI) (Ma et al, 2010),Polyamide (PA or Nylon) (Bourbigot et al, 2002), Polyethersulfone (PES) (Wang et al 2011), Polypropylene (PP) Polystyrene (PS) (Meincke et al,2003) Polytrimethylene terephthalate (PTT) (Hu et al, 2004) and Polyvinyl chloride (PVC) (Awad et al, 2009), etc. As mentioned above the weak www.intechopen.com vander waal force can be overcome at high temperatures, resulting in a homogenized viscous liquid, which can be further moulded into various shapes.…”
Section: Thermoplastic Polymers and Their Nanocompositesmentioning
confidence: 99%
“…Therefore, many publications focused on the compatibility improvement between the filler and the matrix. The influence of the type of cations surrounding the platelets together with the cationic exchange rate has been widely documented [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. For certain polymers, the introduction of a compatibilizer was found to be the successful way to separate the clay platelets in the matrix.…”
Section: Introductionmentioning
confidence: 99%